Effectiveness of Regional Tax Collection and Regional Retribution in North Minahasa Regency in 2014-2017 - Silinaung, Christalia Shella; Rantung, Rinny; Wokas, Heince Ruddy Nicky; Kolibu, Inggrid Juned (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine a descriptive picture of the effectiveness of tax collection and local levies of North Minahasa Regency from 2014-2017. The analysis method in this research is descriptive analysis method with quantitative approach using budget and realization data from DPPKA North Minahasa, and qualitative approach through interviews with realted parties who are responsible for assessing and examining regional finances. The results of this study indicate that the effectiveness of local tax and levy collection in North Minahasa Regency has a different level of effectiveness based on the type of local tax and levy. The government should impove facilities and ifrastructure, and pay attention to existing tax potentials for the effectiveness of tax and levy collection.